Implementasi Pembelajaran Sistem Blok Merdeka Belajar Pada SMKN 1 Cilegon - Utami Pingkan Anggraini; Feri Febrian Syah; Mohamad Rofiq; Marcel Ade Satria; Ilham Akbar Darmawan; Ngadiana Ngadiana (STIKes Ibnu Sina Ajibarang, 2023)
Vocational high schools which produce students ready to enter the world of work require the learning system used to be oriented towards developing students' skill competencies. Through independent learning, SMKN 1 Cilegon implements a block system through teaching factory learning to improve the quality of learning. Teaching Factory is a production-oriented learning that has been adapted to relevant field expertise competencies and is focused on project creation. The method used in this research is a qualitative descriptive method with data collection techniques in the form of literature study, observation and documentation. The findings from this research show that the skills possessed by these students are average, no one is left behind in understanding and adapting all forms of theory and practice so that the involvement of Teaching Factory learning in this block system is very effective.